New records of watermites (Hydrachnidia) collected from macrophyte and Cladophora sp. in South America - Fernandez, Hugo Rafael (2024)
Aquatic mites show a great morphological variability and inhabit a great diversity of freshwater habitats, especially taking advantage of the complexity of resources provided by South American aquatic plants. The relevance of aquatic mites in a microhabitat not studied so far about Amazonian macrophyte plants and Andean filamentous algae is analyzed. A new species of aquatic mite is described, and with it, the genus Piona and Arrenurus amazonicus are recorded for the first time in Colombian rivers; new records of Sperchon neotropicus associated with Cladophora sp. in the Andean subtropical zone of Argentina and Bolivia are reported. The functional classification proposed by Fernández and Fossati-Gaschignard for aquatic mites with their lifestyle and habitat preferences is contrasted and geographically expanded. Contributions such as this one to the knowledge of new species, biological data, and new localities of aquatic organisms are the basis of the urgent agenda of world biodiversity.